THE ROLE OF AMIR TEMUR IN WORLD HISTORIOGRAPHY AND SOURCE STUDIES (Academia Science Repository, 2023)
This article provides information about the role of Amir Temur in World historiography and source studies and the preparation of Amir Temur for military campaigns.